Corporate tax and location choice for multinational firms. Issue 26 (3rd June 2018) - Lawless, Martina; McCoy, Daire; Morgenroth, Edgar L. W.; O"Toole, Conor M.
ABSTRACT: This article examines the effects of corporate tax on these location decisions of newly established multinational subsidiaries across 26 European countries over an 8-year period. We contribute to the existing literature by examining the effects of a non-linear response of firm location decisions to changes in the tax rate. We also show that there are large variations in the sensitivity to tax rates across sectors and firm size groups. In particular, financial sector firms are more than twice as sensitive to changes in corporation tax rates relative to other sectors. Our baseline result is a finding that a 1% increase in the statutory or policy rate of corporation tax would lead to a reduction in the conditional location probability of 0.68%. Using the effective average tax rate, the marginal effect implies a reduction in the location probability of 1.15% following a 1% increase in the tax rate. Although overall tax has the expected negative effect on location probability, the marginal effect of an increase is lower at higher rates of tax.